Renal Protective Effects of Gamma-Mangostin in Streptozotocin-Induced Diabetic Mice - Saikhu Akhmad Husen1,2, Salamun1 , Arif Nur Muhammad Ansori3 , Suhailah Hayaza4 , Raden Joko Kuncoro (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was aimed to investigate the ability of gamma-mangostin to reduce plasma blood urea nitrogen (BUN) and creatinine and ameliorates the impaired renal proximal tubular cells in diabetic mice. Antioxidant assay was conducted by using male BALB/c mice. Mice were divided into two groups, they were normal control (KN) and streptozotocin-induced diabetic mice. Streptozotocin (STZ) induction was performed using multiple low-dose of 30 mg/kg body weight injected for five consecutive days. Diabetic mice have divided into three subgroups; diabetic control (KD), diabetic mice treated with acarbose (KA), and diabetic mice treated with gamma-mangostin. The gamma-mangostin treatment group was categorized based on the dose given; P1 (1 mg/kg BW), P2 (2 mg/kg BW), and P3 (4 mg/kg BW). Interestingly, gamma-mangostin administration was found to be able to lower plasma BUN and creatinine and ameliorate the impaired renal proximal tubular cells in diabetic mice significantly. Therefore, gamma-mangostin has demonstrated high antioxidant activity. The proof suggests that gamma-mangostin is a lead compound candidate for clinical management or prevent diabetes mellitus.